2014
DOI: 10.2337/dc13-2955
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of the SGLT2 Inhibitor Dapagliflozin in Type 1 Diabetes: A Randomized, Double-Blind, Placebo-Controlled Pilot Study

Abstract: OBJECTIVEInsulin adjustments to maintain glycemic control in individuals with type 1 diabetes often lead to wide glucose fluctuations, hypoglycemia, and increased body weight. Dapagliflozin, an insulin-independent sodium-glucose cotransporter 2 (SGLT2) inhibitor, increases glucosuria and reduces hyperglycemia in individuals with type 2 diabetes. The primary objective of this study was to assess short-term safety of dapagliflozin in combination with insulin; secondary objectives included pharmacokinetic, pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
206
4
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(233 citation statements)
references
References 10 publications
20
206
4
3
Order By: Relevance
“…weight, insulin dose, and the incidence of hypoglycemia with canagliflozin treatment are consistent with the effects reported with other SGLT2 inhibitors added on to insulin therapy in patients with type 1 diabetes (17,18). Dose-related reductions in HbA 1c were seen with canagliflozin across phase 3 studies in patients with type 2 diabetes (10), but no dose response was observed in the current study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…weight, insulin dose, and the incidence of hypoglycemia with canagliflozin treatment are consistent with the effects reported with other SGLT2 inhibitors added on to insulin therapy in patients with type 1 diabetes (17,18). Dose-related reductions in HbA 1c were seen with canagliflozin across phase 3 studies in patients with type 2 diabetes (10), but no dose response was observed in the current study.…”
Section: Discussionsupporting
confidence: 76%
“…Several small pilot studies with SGLT2 inhibitors, ranging from 2 to 8 weeks, have been performed in patients with type 1 diabetes (17)(18)(19). These studies have generally shown that treatment with SGLT2 inhibitors provides improved glucose control and reductions in the insulin dose without increasing hypoglycemic events.…”
mentioning
confidence: 99%
“…13 From the limited available data, the risk appears to be firstly of euDKA in type 1 diabetes and in the context of pancreatic (ÎČ-cell) failure. SGLT2 inhibitors were shown to have beneficial effects on glucose profiles with lower daily insulin doses in type 1 diabetes from short term studies 9,14 ; nevertheless, worries regarding ketosis were noted. 15 Recognised precipitating factors for ketoacidosis were noted in the two patients with type 2 diabetes who developed ketoacidosis: poor nutrition and postoperative stress.…”
Section: The Magnitude Of the Problemmentioning
confidence: 99%
“…30 This new class of drugs has already been shown to reduce glycemic levels in animals and humans with type 1 DM (T1DM), in addition to allowing a reduction in insulin dosage. [31][32][33] These drugs could, thus, be used as an adjuvant therapy in the treatment of DM1, with low risk of hypoglycemia and without weight gain. However, this is not yet an approved therapy for T1DM, and further studies are needed to assess the safety of SGLTi-2 in this group of patients.…”
Section: The Kidney As a Treatment Targetmentioning
confidence: 99%